(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2015)
Multi-media applications or multimedia fusion, refers to the integration of more than one media such as text, graphic, animation, audio and video in multi digital environments such as virtual reality, augmented reality and mixed reality. These applications have potential to be effective teaching and learning aids that can enhance understanding and achievement of preschool learners, epecially on topics that are abstract and complex in nature. Results of the statistical analysis on the post test for the Controlled (K) and Experimental (E) groups, showed that there was a significant difference in the learning of the topic on Solar System with the theme Exploring Outerspace by the Experimental group (E) when compared to the Controlled group (K) [t(df=40)=2.895, p=0.008]. The mean indicated for the post test results by the Controlled group (K) was 9.571; and the mean indicated for the post test results by the Experimental group (E) was 11.381. Thus, these findings showed that the achievement of preschool learners from the Experimental group (E) was higher as compared to learners from the Controlled group (K). Aplikasi pelbagai media ataupun multimedia fusion, merujuk kepada hubungan lebih daripada satu media seperti teks, grafik, animasi, audio dan video dalam pelbagai persekitaran digital seperti persekitaran maya, realiti luasan dan realiti campuran. Aplikasi tersebut berpotensi sebagai alat bantu pengajaran dan pembelajaran yang dapat meningkatkan kefahaman dan pencapaian murid prasekolah, terutamanya bagi topik yang berbentuk abstrak dan kompleks. Keputusan analisis statistik terhadap ujian pasca bagi Kumpulan kawalan (K) dan Kumpulan Eksperimen (E) mendapati, terdapat perbezaan pencapaian yang signifikan dalam pembelajaran topik sistem solar bertemakan Meneroka Angkasa di antara Kumpulan Eksperimen (E) berbanding dengan Kumpulan Kawalan (K)[t(df=40)=2.895, p=0.008]. Nilai min ujian pasca bagi Kumpulan Kawalan (K) ialah 9.571; dan nilai min ujian pasca bagi Kumpulan Ekperimen (E) ialah 11.381. Jadi, dapatan ini menunjukkan bahawa pencapaian murid dari Kumpulan Eksperimen (E) adalah lebih tinggi berbanding Kumpulan Kawalan (K).